PENYUSUNAN FORMULAS! PENGGUNAAN PUPUK RAMAH LINGKUNGAN PADA PADI SAWAH UNTUK PERLINDUNGAN LAHAN PERTANIAN SECARA BERKELANJUTAN - I MADE ADNYANA (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2012)
The research was done in the area of subak Tibuhbiyu, Kerambitan District, Tabanan Regency to get the rational suitable fertilizer formulation as a environmentally friendly on rice plant. To achieve these objectives, the research conducted through several activities, namely: soil survey, physical and chemistry of soil analysis, the factorial field experiment of rice plant response for fertilizer treatments, and analysis of the soil quality after harvest. Most of Subak Tibuhbiyu paddy soil was a medium soil fertility status (60%), due to the high value of the cation exchange capacity (CEC) and base saturation (KB). Provision of compost can also reduce the use of NPK fertilizers. The best formulation fertilizer are 10 tons ha-1 compost in combination with 75% of the NPK recommendation, which can provide a high grain yield, ie 7.35 tones ha-1. In general, added of NPK fertilizer, organic fertilizer, or the each other combination, not cause pollution to the soil environment, because its had a medium quality of soil after harvest.